2010
DOI: 10.1002/dys.415
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dyslexics' phonological deficit III: foreign speech perception and production

Abstract: This study investigates French dyslexic and control adult participants' ability to perceive and produce two different non-native contrasts (one segmental and one prosodic), across several conditions varying short-term memory load. For this purpose, we selected Korean plosive voicing (whose categories conflict with French ones) as the segmental contrast and lexical stress as the prosodic contrast (French does not use contrastive lexical stress). We also used a French (native) segmental contrast as a control. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
4
39
1
Order By: Relevance
“…It is more commensurate with proposals that the deficit is in accessing phonological representations (Blomert et al, 2004;Dickie, 2008;Ramus & Szenkovits, 2008;Soroli et al, 2010). According to this latter proposal, it is when phonological tasks place heavy demands on short-term memory, conscious awareness, and time constraints that individuals with dyslexia perform poorly.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…It is more commensurate with proposals that the deficit is in accessing phonological representations (Blomert et al, 2004;Dickie, 2008;Ramus & Szenkovits, 2008;Soroli et al, 2010). According to this latter proposal, it is when phonological tasks place heavy demands on short-term memory, conscious awareness, and time constraints that individuals with dyslexia perform poorly.…”
Section: Discussionsupporting
confidence: 50%
“…Yet another hypothesis would be that they do not have degraded phonological representations (Ramus & Szenkovits, 2008;Soroli et al, 2010), or at least not at the segmental level (van der Lely & Marshall, 2011). This would predict no difference with the control children.…”
Section: Predictionsmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, impaired neural entrainment to low-frequency amplitude envelopes should affect the accurate representation of syllable stress and syllable boundaries (Goswami, 2011, Goswami, 2015), impairments that indeed characterise children with dyslexia in some languages (Goswami, Mead, et al, 2013 for English; Jiminez-Fernandez, Gutierrez-Palma, & Defior, 2014 for Spanish, see also Soroli, Szenkovits, & Ramus, 2010 for French [dyslexic adults]). Further, impairments in the auditory processing of amplitude envelope rise times (perceptual cues to modulation rates) are found in children with dyslexia in many languages (to date, Finnish, Spanish, Chinese, English, French, Dutch and Hungarian, Goswami, 2011, Goswami, 2015, for recent summaries).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on adult participants provided a partial replication, finding a striking dissociation between deficits in the awareness of prosodic patterns (using a version of the DeeDee task) and spared automatic processing of prosody, as measured by a task that did not explicitly bear on prosodic patterns, but that used speech material whose prosody was either congruent or incongruent (Mundy, 2011;Mundy & Carroll, in press). Finally, another study on adults reported difficulties in perceiving and producing foreign stress patterns, but that seemed to be entirely explained by the metaphonological nature of the task and by short-term memory load (Soroli, Szenkovits, & Ramus, 2010). Thus, it seems that deficits in prosody perception or production are found in individuals with dyslexia only to the extent that the tasks used involve metalinguistic judgements or other difficulty factors.…”
Section: Patterns Of Normal and Abnormal Performance In Developmentalmentioning
confidence: 96%